P142 Lodderomyces elongisporus: A n emerging cause of fung emia. (20th September 2022) - Kaur, Harsimran; Gupta, Parakriti; Shankarnarayan, Shamanth; Pandey, Abhishek; Ghosh, Anup; Chakrabarti, Arunaloke; Rudramurthy, Shivaprakash
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM:   Background: Lodderomyces elongisporus, earlier considered as a sexual state of Candida parapsilosis, was described as a distinct species based on ribosomal RNA gene sequencing. Few cases of human infections by this yeast have been described from Mexico, China, Malaysia, Kuwait, Australia, and the USA. We describe here eight cases of fungemia by L. elongisporus from a tertiary care hospital in North India. Methods: Clinical characteristics and risk factors associated with L. elongisporus fungaemia were evaluated. Yeast isolated from blood culture (BD BACTEC™ 9240, New Jersey, USA) was identified by matrix-assisted laser desorption/ionization time-of-flight mass spectroscopy (MALDI-TOF MS, Bruker Daltonik GmbH, Bremen, Germany) and sequencing of D1/D2 region of a large subunit of ribosomal DNA. We performed antifungal susceptibility testing for amphotericin B, fluconazole, itraconazole, voriconazole, posaconazole, caspofungin, anidulafungin, and micafungin by the microbroth dilution method recommended by the Clinical and Laboratory Standards Institute (CLSI). Results: We report eight cases of fungemia caused by L. elongisporus at our tertiary care center. Of these, three were infants (males) and five were adults (3 males and 2 females). The mean age of adults was 43.4 years. Among the pediatric cases, underlying diseases included congenital heart disease/atrophic kidney (neonate), tracheoesophageal fistula (4 months), and late-onset neonatal sepsis (LONS). Among the adults, underlying illnesses included acute kidney injury ( n  = 2), superior mesenteric artery thrombosis with bowel gangrene ( n  = 1), diabetes ( n  = 1), and central nervous system (CNS) lymphoma ( n  = 1). The iatrogenic factors included the history of surgery ( n  = 3), admission to ICU ( n  = 3), presence of urinary catheter ( n  = 4), and presence of central venous catheter ( n  = 1). Seven patients were on broad-spectrum antibiotics. The mean stay in the hospital was 20.38 days. Three of the patients were managed with fluconazole. Six patients improved while one left against medical advice (LAMA) and one expired. The range of minimum inhibitory concentration (MIC) of all the isolates against antifungals was as follows: amphotericin B (0.03-0.25  μ g/ml), fluconazole (0.125  μ g/ml), voriconazole (0.03  μ g/ml), itraconazole (0.03-0.06  μ g/ml), posaconazole (0.03-0.25  μ g/ml), caspofungin (0.03-0.06  μ g/ml), micafungin (0.03-0.06  μ g/ml), and anidulafungin (0.03  μ g/ml). Conclusion: Lodderomyces elongisporus is an emerging pathogenic yeast causing fungemia in patients with comorbidities and undergoing surgery or invasive interventions. Though no antifungal breakpoints exist for this yeast, all the isolates exhibited low MICs to all the tested antifungals.